The Ethical Journey of The March Sisters: A Study in Morality and Growth - Girsang, Martina; Ardauli, Cindy (Holistic Science, 2025)
Louisa May Alcott’s Little Women (1868) remains a cornerstone of American literature, depicting the challenges and growth of four March sisters—Jo, Meg, Beth, and Amy—during the American Civil War. This paper explores central themes in the novel, focusing on the tension between individual desires and societal expectations, particularly regarding women’s roles in the 19th century. Alcott addresses how each sister grapples with personal and societal pressures: Jo rejects traditional gender roles in favor of independence and writing, while Meg embraces femininity and marriage. The paper also examines the moral and emotional conflicts faced by the characters as they balance personal ambitions with family obligations. By analyzing character development, symbolism, and narrative structure, the study demonstrates how Little Women is not only a reflection of its time but also a timeless exploration of family, identity, and the pursuit of happiness. The novel's examination of feminine duty and domesticity continues to resonate with contemporary debates on gender and societal roles.